Respon Dunia Barat Terhadap Ekonomi Syariah Di Era Revolusi Industri 4.0 - Ahyani, Hisam; Slamet, Memet (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2022)
Sharia economic opportunities developed in Indonesia need to be supported by knowing the western response to the economic conditions in Indonesia, where the revolutionary era 4.0 is a challenge for Indonesia in the economic welfare of its people. This study aims to determine the response and contribution of the west to the Islamic economy in Indonesia in the Industrial Revolution Era 4.0. This type of research is juridical normative and the nature of the research is descriptive legal study. The results of the study found that the response and contribution of the west to the Indonesian sharia economy is to embrace the Indonesian sharia economy with the aim of regaining control of the Indo Pacific, by implementing a free market and capitalist system. However, Indonesia remains in principle, namely developing the potential of the Islamic economy because this is a golden opportunity for a prosperous Indonesia. Abstrak Peluang Ekonomi Syariah yang dikembangkan di Indoensia perlu didukung dengan mengetahui respon barat terhadap kondisi ekonomi di Indonesia, dimana era revolusi 4.0 menjadi tantangan tersendiri bagi Indonesia dalam mensejahterahkan ekonomi masyarakatnya. Penelitian ini bertujuan guna mengetahui respon dan sumbangsih barat terhadap ekonomi syariah di Indonesia Era Revolusi Industri 4.0. Jenis penelitian ini dalah yuridis normative dan Sifat penelitian descriptive legal study. Hasil penelitian ditemukan bahwa respon dan sumbangsih barat terhadap ekonomi syariah Indonesia yaitu merangkul ekonomi syariah Indonesia dengan tujuan menguasai kembali indo pasifik, dengan menerapkan sistem pasar bebas dan kapitalis. Namun Indonesia tetap pada prinsipnya yaitu mengembangkan potensi ekonomi syariah karena ini adalah peluang emas menuju Indonesia sejahtera.